2003
DOI: 10.1097/00004032-200309000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Lung and Larynx Cancers in Coal Mines in Upper Silesia—preliminary Results

Abstract: The results of the preliminary analysis of the risk of lung and larynx cancers among coal miners in Upper Silesia are presented. The risk increases substantially during the work under conditions of short-lived radon progeny hazard, especially when the concentration of alpha potential energy of short-lived radon progeny is higher than 2.5 (microJ m(-3)) that corresponds to the possibility of receiving the effective dose higher than 6 mSv y(-1). Significant differences of the risk are noticed between sub-populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
0
10
0
4
Order By: Relevance
“…Another study in the United States comparing 3,792 lung cancer cases to 1,966 colorectal cancer cases that were used as controls, found a suggested increased risk of lung cancer among coal miners (Swanson et al, 1993). Working as a coal miner was also reported to be associated with increased risk of lung cancer in Europe (Skowronek and Zemla, 2003). Three smaller case–control studies in the United States and Europe; however, found no evidence of this association (Ames et al, 1983; Meijers et al, 1988; Jockel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study in the United States comparing 3,792 lung cancer cases to 1,966 colorectal cancer cases that were used as controls, found a suggested increased risk of lung cancer among coal miners (Swanson et al, 1993). Working as a coal miner was also reported to be associated with increased risk of lung cancer in Europe (Skowronek and Zemla, 2003). Three smaller case–control studies in the United States and Europe; however, found no evidence of this association (Ames et al, 1983; Meijers et al, 1988; Jockel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous health effects associated with underground coal mining have been studied, including pneumoconiosis, tuberculosis, chronic obstructive pulmonary disease (COPD), and other nonmalignant diseases of the lung (Merchant et al, 1986; Kuempel et al, 1995; Isidro et al, 2004). Studies evaluating the risk of lung cancer among underground coal miners have reported conflicting results (Ames et al, 1983; Meijers et al, 1988; Morabia et al, 1992; Swanson et al, 1993; IARC Monographs on the Evaluation of the Carcinogenic Risks to Human 1997; Jockel et al, 1998; Skowronek and Zemla, 2003; Hoffmann and Jockel, 2006; Attfield and Kuempel, 2008; Miller and MacCalman, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Halbwertszeit der Isotope hat wesentliche Bedeutung für die Möglichkeit ihrer Verbreitung in der natürlichen Umwelt. Wenn es um den radiologischen Schutz geht, ist Radon Rn-222 am wichtigsten, das Edelgas mit der längsten Halbwertszeit, nämlich 3 Tage, 19 Stunden und 48 Minuten (Zerfallskonstante l = 7,55 • 10 -3 • h -1 ). Radon Rn-222 stammt direkt aus dem am meisten verbreiteten Radisotop Ra-266.…”
Section: Radon -Einführungunclassified
“…O monitoramento da concentração do 222 Rn em ambientes fechados precisa da medida separada da atividade deste gás e de seus produtos de decaimento (filhos), que são os verdadeiros responsáveis pela dose recebida no aparelho respiratório [2,13,17,49].É por esse motivo que necessitamos de um arranjo que hospede o detector de partículas alfa LR-115 II e também seja capaz de atuar como separador, além de obter atividades integradas em muitos meses de exposição, e de ter características pouco dependentes da taxa de ventilação.…”
Section: Monitor De Placas Paralelasunclassified